The impact of external financing during wartime on the economy of a country in war - Davydiuk, Tetiana; Shymanska, Kateryna (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This study delves into the effects of external financial support (official development assistance and foreign direct investments) on economic activity and welfare based on data from five nations injured by similar military conflicts from 2006 to 2021. Focusing on Ukraine, the research recommends ways for policymakers to navigate external financing during wartime. The employment rate, GDP per capita, inflation rate, and exports are the foundations for our analysis. The methodological approach employed regression analysis to measure the economic effect of external financing in wartime in these conflict-ridden nations. The findings reveal that increased foreign direct investment during wartime correlates with reduced employment rates, heightened GDP per capita, and increased exports. In addition, the negative impact of official development assistance ODA on employment was found, and it had a positive effect on exports but no significant effects on GDP per capita. A statistically significant impact on the inflation rate was not seen.